Time-dependent postural control adaptations following a neuromuscular warm-up in female handball players: a randomized controlled trial - Steib, Simon; Zahn, Peter; Eulenburg, Christine Helene, Gräfin zu; Pfeifer, Klaus; Zech, Astrid (BMC sports science, medicine & rehabilitation, 2016)
Female handball athletes are at a particular risk of sustaining lower extremity injuries. The study examines time-dependent adaptations of static and dynamic balance as potential injury risk factors to a specific warm-up program focusing on neuromuscular control.
Gesehen am 15.09.2023